2019
DOI: 10.1093/bjc/azz011
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Domestic Abuse and Drug and Alcohol Dependency

Abstract: This article elucidates the dynamics that occur in relationships where there have been both substance use and domestic abuse. It draws interpretively on in-depth qualitative interviews with male perpetrators and their current and former partners. These interviews were undertaken for the National Institute for Health Research-funded ADVANCE programme. The article’s analysis highlights the diverse ways in which domestic abuse by substance-using male partners is compounded for women who have never been substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…The co-occurrence of problematic substance use and domestic abuse victimisation among women is an international problem (Gadd et al, 2019;Weaver et al, 2015;Devries et al, 2013). Studies from countries including, Australia, South Africa, Spain, Japan, the USA and Sweden have shown that DAV is a common experience among women with PSU (Ahmadabadi et al, 2019;Watt et al, 2017;Gilchrist et al, 2012;Yoshihama et al, 2010;Hughes et al, 2010;Stene et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The co-occurrence of problematic substance use and domestic abuse victimisation among women is an international problem (Gadd et al, 2019;Weaver et al, 2015;Devries et al, 2013). Studies from countries including, Australia, South Africa, Spain, Japan, the USA and Sweden have shown that DAV is a common experience among women with PSU (Ahmadabadi et al, 2019;Watt et al, 2017;Gilchrist et al, 2012;Yoshihama et al, 2010;Hughes et al, 2010;Stene et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…"He said, she said "-Valuing Both Partners' Accounts: Critical Reflective Lens and Theoretical Stance To compare narratives in the analysis and to provide a synthesis of male and female (current or former partner) accounts, timelines for each participant were first created to map out the chronology of events. Case studies in the style of "pen portraits" were then written for each participant aiming to highlight "apparent contradictions, avoidances and implausible claims" (Gadd et al, 2019(Gadd et al, , p. 1040, before combining these to provide an overall picture of the relationship. We were thus able to see where accounts were similar and where they diverged and were discrepant, to understand how women and men might view and understand their relationship differently in relation to the substance use and intimate partner abuse.…”
Section: Researchers' Felt Experiences Of Interviewingmentioning
confidence: 99%
“…This association is significantly stronger from men who abuse or are dependent on alcohol or drugs [16]. The complex interplay between substance use and IPA perpetration includes intoxication (change or disinhibition when under the influence of alcohol or stimulant drugs), withdrawal and craving (irritability and frustration or the need to acquire substances), the impact of substance use on relationships, the wider dynamics of power and control, and psychological vulnerabilities (adverse childhood experiences, mental health, and emotional instability) linked to substance use and IPA [17,18]. At least 3 in 10 men receiving substance use treatment have been physically or sexually violent, and 7 in 10 men have been psychologically abusive towards their partner in the previous year [3,8,9,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Some interventions to address IPA in men who use substances present a simplistic model of inebriated physical violence and struggle to integrate issues of gender, non-physical abuse and to fully consider the impact of a substance use lifestyle. Recent research has identified that it is not one factor that explains causal pathways into IPA, but rather a multilevel and multifactor explanation is required [17,18,30]. A nested ecological model identifies factors at 4 levels, including structural factors such as patriarchy, subcultural factors, for example, high tolerance for general alcohol use, familial factors, including modelling from family of origin and social learning theory, and individual factors such as high anger or high impulsivity [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation